2009 International Conference on Power Electronics and Drive Systems (PEDS) 2009
DOI: 10.1109/peds.2009.5385877
|View full text |Cite
|
Sign up to set email alerts
|

Practical deployment of the Brushless Doubly-Fed Machine in a medium scale wind turbine

Abstract: --The Brushless Doubly-Fed Machine (BDFM) is a brushless electrical generator which allows variable speed operation with a power converter rated at only a fraction of the machine rating. This paper details an example implementation of the BDFM in a medium-scale wind turbine. Details of a simplified design procedure based on electrical and magnetic loadings are given along with the results of tests on the manufactured machine. These show that a BDFM of the scale works as expected but that the 4/8 BDFM chosen wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Referring to (2), if the chording factors and the distribution factors of the tooth harmonics are equal to those of the fundamental component, then k wv = k w 1 . The νth harmonic order MMF of each phase winding can be expressed as follows:…”
Section: Tooth Harmonic Winding Theory Accordingmentioning
confidence: 99%
“…Referring to (2), if the chording factors and the distribution factors of the tooth harmonics are equal to those of the fundamental component, then k wv = k w 1 . The νth harmonic order MMF of each phase winding can be expressed as follows:…”
Section: Tooth Harmonic Winding Theory Accordingmentioning
confidence: 99%
“…The authors have successfully demonstrated a smallscale BDFM in a working 20 kW wind turbine [3] and have built a 250 kW prototype in a frame size D400 involving construction and winding techniques appropriate to large machines that has undergone witnessed tests over its full load and speed range. Other groups also have reported large BDFMs, for example in Brazil with a 75 kW machine [4] The research leading to these results has received funding from the European Union ' and China with the design of a 200 kW machine [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the BDFIG is likely to have a lower cost than that of an equivalent DFIG due to the absence of the slip ring system and simpler structure of the rotor winding. To date, a 20 kW BDFIG-based wind turbine has been erected to confirm its feasibility in wind power applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…voltage, current and flux ω 1 , ω 2 , ω r angular frequency of power winding, control winding and rotor θ 1 , θ r angular position of power winding flux frame and rotor p 1 , p 2 pole pair numbers of power winding and control winding R s1 , R s2 , R r resistance of power winding, control winding, and rotor L s1 , L s2 , L r self-inductance of stator winding and rotor L s1r , L s2r coupling inductance between power winding and rotor…”
mentioning
confidence: 99%